Squaramide-Catalyzed Asymmetric Michael Addition/Cyclization Reaction for the Synthesis of Chiral Bisspiro Barbituric Acid–Oxindole Derivatives - Qiao, De-Jun; Du, Da-Ming (Molecules (Basel, Switzerland), 2025)
An efficient stereoselective strategy for the synthesis of chiral bisspiro barbituric acid–oxindole derivatives was developed. The asymmetric Michael addition/cyclization tandem reaction between benzylidene barbituric acids and oxindolylmalonitriles was catalyzed by squaramide catalyst, and the corresponding spirocyclic products were obtained in good-to-high yields (up to 97%) with excellent stereoselectivities (up to >99% ee, >20:1 dr). At the same time, the practicality of the reaction was verified by the gram-scale preparation reaction.